Total synthesis of atropurpuran - Jing Gong (Nature Portfolio, 2016)
Polycyclic and caged molecules are common in nature but present challenging targets for synthesis. Here, the authors report a route to caged diterpene cores and apply to the total synthesis of atropurpuran, with oxidative dearomatization/intramolecular Diels-Alder cascade, aldol and ketyl-olefin cyclizations as key steps.